1997
DOI: 10.3164/jcbn.22.113
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Phyllanthus fraternus against Thioacetamide-Induced Mitochondrial Dysfunction.

Abstract: SummaryThe effect of administration of thioacetamide on rat liver mitochondrial functions and the protective effect of an aqueous extract of Phyllanthus fraternus against thioacetamide-induced damage were studied. When rats were treated with thioacetamide, the rate of mitochondrial respiration was decreased significantly with both NAD+ linked and FAD linked substrates, and the respiratory control ratio, an index of membrane integrity and the P/O ratio, a measure of phosphorylation efficiency, decreased signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Venkateswaran et al (1987) reported that P. niruri inhibited the replication of woodchuck hepatitis virus in vivo and decreased its pathological effect on woodchuck liver. Human clinical studies have been carried out with P. niruri (Thyagarajan et al, 1988) and it has been shown that it has potent activity against various hepatic disorders such as viral hepatitis and toxicity caused by different drugs and environmental toxicants (Unander et al, 1995;Padma and Setty, 1999). However, the mechanisms responsible for this hepatoprotective action of P. niruri are not yet well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Venkateswaran et al (1987) reported that P. niruri inhibited the replication of woodchuck hepatitis virus in vivo and decreased its pathological effect on woodchuck liver. Human clinical studies have been carried out with P. niruri (Thyagarajan et al, 1988) and it has been shown that it has potent activity against various hepatic disorders such as viral hepatitis and toxicity caused by different drugs and environmental toxicants (Unander et al, 1995;Padma and Setty, 1999). However, the mechanisms responsible for this hepatoprotective action of P. niruri are not yet well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of the aqueous extract of the Phyllanthus fraternus significantly decreased the thioacetamide (Padma and Setty, 1997) or carbon tetrachloride (Padma and Setty, 1999) induced lipid peroxidation in vivo and protected the liver from the hepatotoxin-induced toxicity. Co-administration of amla (Emblica officinalis) with dimethyl hydrazine significantly reduced the cytotoxic products such as MDA and conjugated dienes (Anila kumar et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…It was reported earlier from our laboratory that mitochondrial dysfunction caused by the administration of an alcohol (Sebastian and Setty, 1999) or thioacetamide (Padma and Setty, 1997) or carbon tetrachloride (Padma and Setty, 1999) could be prevented by prior administration of aqueous extract of Phyllanthus fraternus. This study mainly involved on mitochondrial function and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although a number of reports described the usefulness of this herb against the adverse effects of various drug and toxicants (18)(19)(20)(21), no studies have been published to date, describing its beneficiary role against nimesulide-induced hepatotoxicity. The anti-inflammatory drug, nimesulide is a selective cyclooxygenase-2 (COX-2) inhibitor, with only residual activity against cyclooxygenase-1 (COX-1) (22,23).…”
Section: Introductionmentioning
confidence: 99%